Mechanistic Targets and Nutritionally Relevant Intervention Strategies to Break Obesity–Breast Cancer Links - Bustamante-Marin, Ximena M.; Merlino, Jenna L.; Devericks, Emily; Carson, Meredith S.; Hursting, Stephen D.; Stewart, Delisha A. (Frontiers in Endocrinology, 2021)
The worldwide prevalence of overweight and obesity has tripled since 1975. In the United States, the percentage of adults who are obese exceeds 42.5%. Individuals with obesity often display multiple metabolic perturbations, such as insulin resistance and persistent inflammation, which can suppress the immune system. These alterations in homeostatic mechanisms underlie the clinical parameters of metabolic syndrome, an established risk factor for many cancers, including breast cancer. Within the growth-promoting, proinflammatory milieu of the obese state, crosstalk between adipocytes, immune cells and breast epithelial cells occurs via obesity-associated hormones, angiogenic factors, cytokines, and other mediators that can enhance breast cancer risk and/or progression. This review synthesizes evidence on the biological mechanisms underlying obesity-breast cancer links, with emphasis on emerging mechanism-based interventions in the context of nutrition, using modifiable elements of diet alone or paired with physical activity, to reduce the burden of obesity on breast cancer.